2019
DOI: 10.1186/s40792-019-0610-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic completion gastrectomy in elderly patients with remnant gastric cancer: a case series

Abstract: Background Open completion gastrectomy (OCG) has been selected to treat remnant gastric cancer (RGC) due to severe adhesions and difficulty recognizing anatomical orientation after primary gastrectomy. In general, elderly individuals’ physiological reserves gradually decrease. Moreover, elderly patients (EPs) often have multiple complicating factors (i.e., frailty and comorbidities), leading to more postoperative complications after abdominal surgery. Recently, several trials revealed the advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Six studies reported that the conversion rate to open gastrectomy was 5.6-47.1%; the other 15 studies reported no cases of conversion to open gastrectomy. In all studies, the mean operation time ranged from 197 to 487 min, the mean blood loss was up to 425 g, the mean number of retrieved lymph nodes ranged from 7 to 26 and the mean duration of postoperative hospital stay (18)(19)(20)(21)(22)(23)(24). Among these 8 studies, 6 studies showed that LTG was associated with less blood loss, 4 studies showed that LTG was associated with a longer operation time, and 1 study showed that LTG was associated with a greater number of retrieved lymph nodes and shorter postoperative hospital stay in comparison to the OTG group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported that the conversion rate to open gastrectomy was 5.6-47.1%; the other 15 studies reported no cases of conversion to open gastrectomy. In all studies, the mean operation time ranged from 197 to 487 min, the mean blood loss was up to 425 g, the mean number of retrieved lymph nodes ranged from 7 to 26 and the mean duration of postoperative hospital stay (18)(19)(20)(21)(22)(23)(24). Among these 8 studies, 6 studies showed that LTG was associated with less blood loss, 4 studies showed that LTG was associated with a longer operation time, and 1 study showed that LTG was associated with a greater number of retrieved lymph nodes and shorter postoperative hospital stay in comparison to the OTG group.…”
Section: Resultsmentioning
confidence: 99%
“…This means that laparoscopic surgery takes longer to perform, but also that even under severe adhesion, laparoscopic surgery with a magnified view and technical advances may contribute to the performance of a safe and secure operation for RGC. Only 4 reports including our own have described long term clinical outcomes, and all of these studies indicated comparable survival rates between LTG and OTG groups (18,19,24). However, conclusions have not been reached because of the short follow-up time periods (median 21-39.1 months).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, we reviewed all published English language literature on LG for RGC to better characterize the technical aspects of the currently used procedures (Table 3). Recently, ten non-RCT studies with a small series of patients compared the perioperative results of LG for RGC with those of open gastrectomy (OG)[60-69].…”
Section: Laparoscopic Gastrectomy For Remnant Gastric Cancermentioning
confidence: 99%
“…All studies comparing the operating time between OG and LG reported that LG required more time than OG, even though the difference was not statistically significant in five out of the ten studies[64-66,68,69]. However, LG was associated with lower intraoperative blood loss than OG in six of the ten studies[60,61,65,66,68,69]. The number of resected lymph nodes was reported in all non-RCTs and case studies.…”
Section: Laparoscopic Gastrectomy For Remnant Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation